THE EFFECT OF DOMESTIC VIOLENCE IN TERMS OF WOMEN’S MENTAL HEALTH DURING COVID-19 PANDEMIC (Practitioner Research, 2022)
The most common issue throughout this pandemic is domestic violence. Women are the most victims of domestic violence during the Covid-19 pandemic. Domestic violence is a pattern of aggression, torture, or harassment used to retain authority over a spouse in a close relationship. Around 57% of domestic violence cases were reported from women during Movement Control Order in Malaysia. The objective of this study is to identify the effect on the issue of domestic violence during the Covid-19 pandemic. The researchers employed quantitative approaches to collect long-term data on domestic violence incidents during the COVID-19 Pandemic with four registered counselors from the National Population and Family Development Board (LPPKN) and the Department of Social Welfare. According to the counselor’s perspective, the study’s findings show several effects of domestic violence during the Covid-19  pandemic.